The Influence of Innovative Behavior and Teacher Competence on the Learning Motivation of Senior High School Students in Talang Kelapa District - Yenny Maryati; Bukman Lian; Andi Rahman (Asosiasi Riset Ilmu Pendidikan Indonesia, 2025)
This study aims to find out and describe the Influence of Innovative Behavior and Teacher Competence on the Learning Motivation of High School Students in Talang Kelapa District. The method used in this study is a descriptive quantitative method, where data is collected, compiled and processed so that it can be presented in an interesting way to be able to provide an overview of the problem measured so that conclusions can be drawn. The sample of this study is 93 teachers in high schools in Talang Kelapa district. From the results of the study, it was found that: (1) there was an influence between innovative behavior on the learning motivation of high school students in Talang Kelapa District. (2) there is an influence between teacher competence on the learning motivation of high school students in Talang Kelapa District. (3) there is an influence of innovative behavior and teacher competence together on the learning motivation of high school students in Talang Kelapa District. The results obtained provide evidence that the increase in innovative behavior and teacher competence will have an impact on increasing the learning motivation of high school students in Talang Kelapa District.